Asthma phenotypes and lung function up to 16 years of age—the BAMSE cohort. Issue 6 (9th March 2015) - Hallberg, J.; Thunqvist, P.; Schultz, E. S.; Kull, I.; Bottai, M.; Merritt, A.‐S.; Chiesa, F.; Gustafsson, P. M.; Melén, E.
Abstract: Background: Asthma is a disease affecting many locations throughout the airway. Most studies have used spirometry as the primary assessment of airway obstruction, a method that may be less sensitive in regard to peripheral airway obstruction. The aim of this study was to elucidate the associations between asthma phenotypes based on age of onset and duration of symptoms, and (i) spirometry and (ii) small airway involvement measured by impulse oscillometry (IOS) in adolescence. Methods: Children and adolescents taking part in BAMSE, a prospective birth cohort study, performed spirometry at 8 and 16 years and IOS at 16 years of age. Based on data collected in questionnaires, children were categorized into the following groups: 'never asthma', 'early transient asthma', 'early persistent asthma', and 'late onset asthma'. Results: Compared with the never asthma group, all asthma groups were associated with lower FEV1 at 16 years of age (early transient—119 ml, 95% confidence interval −204 to −34; early persistent—410 ml, 95%CI −533; −287; and late onset—148 ml, 95%CI −237; −58). Between 8 and 16 years, significantly less increase in FEV1 was observed in the early persistent and late onset groups. The small airway index 'R5–20 ' was significantly associated with active asthma at 16 years, but not transient asthma. Conclusions: All asthma phenotypes studied were negatively associated with FEV1 in adolescence. IOS measurements indicated that active asthma could be associated with small airway impairments. These results provide new insights into the physiology underlying wheezing phenotypes based on age of onset and duration of disease.